Are maternal health conditions during pregnancy and early-childhood complex chronic conditions associated with entry into care after age five? A population-wide longitudinal study using routinely collected linked administrative data in Scotland - Gedeon, Edit; Craig, Peter; Pearce, Anna; Allik, Mirjam (International Journal of Population Data Science, 2026)
Families who face pregnancy or birth complications or complex childhood health conditions may experience an increased risk of entry into care by placing sustained strain on families. We aimed to assess this, focussing on maternal health conditions that have the potential to cause complications during pregnancy or birth, and complex chronic conditions (CCCs) in early childhood. Maternity, health, and social care data were linked for children born in Scotland between 1996 and 2004. Children who entered care before age five were excluded, and the cohort (N = 380,041; including 5,055 care-experienced children, 1.33%) was followed from birth until 2022. Exposures were two binary variables: any maternal health conditions during pregnancy (e.g. hypertension, diabetes, infections) and any hospitalisations due to CCCs before age 5. The outcome captured first entry into care after age 5 during follow-up. We use modified Poisson regression models to estimate risk ratios (RRs) and 95% CIs for entry into care after age five, adjusting for sex, maternal age and smoking, parity, birth year, deprivation, rurality, and antenatal booking date. The most prevalent CCCs among both care-experienced children and their peers were metabolic/endocrine, respiratory, and neurological conditions. Maternal health problems (RR 1.15, 95% CI 1.07–1.24) and CCCs (RR 1.22, 95% CI 1.15–1.30) were both associated with increased risk of entering care. Our study highlights the importance of providing greater support for families managing health conditions as early as possible in the child’s life course, as this may help keep families together